The Use of Antibodies in Small-Molecule Drug Discovery. (July 2014) - Marsden, Catherine J.; Eckersley, Sonia; Hebditch, Max; Kvist, Alexander J.; Milner, Roy; Mitchell, Danielle; Warwicker, Juli; Marley, Anna E.
Antibodies are powerful research tools that can be used in many areas of biology to probe, measure, and perturb various biological structures. Successful drug discovery is dependent on the correct identification of a target implicated in disease, coupled with the successful selection, optimization, and development of a candidate drug. Because of their specific binding characteristics, with regard to specificity, affinity, and avidity, coupled with their amenability to protein engineering, antibodies have become a key tool in drug discovery, enabling the quantification, localization, and modulation of proteins of interest. This review summarizes the application of antibodies and other protein affinity reagents as specific research tools within the drug discovery process.